The Orthodontict Treatment Effect of Lower Incisors Proclination on Gingival Recession (A Literature Riew) - Karunia, Dyah (The Indonesian Journal of Dental Research)
The aim of orthodontic treatment is to obtain healthy, stable, and aesthetically sufficient occlusion. To achieve these objectives, malposititon teeth should be moved mesio-distally, labio-lingually, or proposed retroclination-proclination to an ideal position. Lower Incisor proclination is labially teeth movement to obtain normally dental arch, good of relation with upper teeth, and aesthetic. Orthodontic treatment effect of lower incisors proclination on gingival recession is still controversial. This paper is aimed to discuss the effects of lower incisors proclination on gingival recession. Condition of periodontal tissues is influenced by number of factors, namely individual variations in tissue morphology and their responses, applied pressure type, poor oral hygiene, age, minimal attached gingival, tooth malposition, fenestration, poor oral hygiene, alveolar bone defects, as well as mechanical trauma such as orthodontic treatment. Gingival recession has close relationship with anatomy structure, such alveolar bone thickness and height, gingival thickness and texture, as well as tooth position. Study on 11-15 years old subjects, grouped into 3, and treated with fixed appliance, removable appliance, and activator showed different depth increases in gingival sulcus during the treatment. The worst inflammation symptoms occurred in patients treated with fixed appliances. Boyd studies on periodontal status of adults, youths, and juveniles using fixed appliance showed no significant gingival recession. Condition of thin and delicate texture gingival as well as thin alveolar plate bone support is more sensitive to gingival recession than thick and fibrous gingival, supported by thick alveolar bone. When teeth which supported by very thin alveolar plate is moved labially (proclined) from jaw, gingival recession would occur. Thin supporting bone can cause release of attached gingival, resulting in recession. Tooth with adequate/normal attached gingival can undergo local recession during orthodontic treatment. It relates with excessive orthodontic force application, which impedes recovery or remodel of the alveolar bone. Based on reported results by various authors, it can be concluded that lower incisors proclination does not always cause gingival recession. It depends on several predisposition factors, including anatomy of very thin cortical alveolar bone plate, narrow attached gingival/keratin, inadequate/thin gingival structure, labially positioned lower Incisors, excessive orthodontic forces for proclination movement, far distance of proclination movement, poor oral hygiene, and age. These factors must be considered in developing treatment planning in order to avoid unnecessary risks and achieve optimal and satisfying treatment objectives.